Integrative analysis of protein-protein interaction networks: linking cellular functions to cancer and diabetes mechanisms - Kumar, Suresh; Vivek; Sharma, Vivek Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Protein-protein interactions (PPIs) are vital in regulating cellular functions, including signal transduction, metabolic control, and intracellular transport. In diseases such as diabetes and cancer, analyzing PPI networks provides valuable insights into underlying molecular mechanisms and potential therapeutic targets. Focusing on disease-specific subnetworks enables the identification of key proteins and their functional relationships. Methods: A subset of the human PPI network associated with diabetes and cancer was analyzed to identify proteins involved in signaling, trafficking, and metabolism. Proteins such as ARF5, M6PR, FKBP4, CYP26B1, NDUFAF7, and FUCA2 were included in the dataset annotations. We utilized visualization techniques to generate PPI (protein-protein interaction) maps, isolate diabetes modules with key genes like INS, GCK, IGF1, PPARG, and GLUT4, and investigate their relationships with different cancer types using the adjusted p-value threshold. Results: In this study, each protein contributed a unique aspect and function to the overall analysis. M6PR regulated the transport of lysosomal enzymes, while ARF5 played a role in Golgi-associated vesicle trafficking. Hormone receptor microtubule FCBP4, along with hormone-receptor microtubule dynamics, was involved in retinoic acid metabolism and germ cell development. NDUFAF7 played a crucial role in mitochondrial complex I assembly, while FUCA2 participated in glycoprotein catabolism. Furthermore, the diabetes-specific interaction modules revealed a core regulatory axis, which comprised INS, GCK, IGF1, PPARG, and GLUT4. These genes are significant insulin signaling and glucose metabolism genes. Beside that, notable associations were observed with endometrial, melanoma, and colorectal cancers. Conclusions: Recording the interplay of metabolic pathways underscores the importance of ppi subnetworks in metabolic regulation, signal transduction, and associated disorders, which supports further drug target investigations in diabetes and cancer.